دراسة تأثير حجم الحبة ووزنها في بعض الخصائص الفينولوجية والمورفولوجية عند بعض أصناف القمح القاسي تحت ظروف المنطقة الساحلية (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة على ثلاثة أصناف من القمح القاسي (شام1، شام3، بحوث 5) إضافة إلى الصنف الشاهد (حوراني) من حيث تأثير ثلاثة مستويات (S, M, L) لحجم الحبّة ووزن الألف حبّة على المراحل الفينولوجية والصفات المورفولوجية. أظهرت الدراسة وجود علاقة إيجابية بين حجم الحبّة ووزنها من جهة وبين نسبة الإنبات المخبري والحقلي، وطول غمد الريشة، وسرعة النمو الأولي (بعد شهر من الإنبات)، وتزامن الإشطاء، والنضج المبكر من جهة ثانية   في معاملات الصنف الواحد وبين الأصناف، وخاصة عند المعاملة (L). تباينت المعاملات الثلاث ضمن الصنف الواحد بفروق معنوية في صفة عدد الإشطاءات في النبات الواحد، وكانت غير معنوية بين الأصناف في حدود المعاملة الواحدة، وقد تفوق الصنف بحوث 5 في عدد الإشطاءات والباكورية، وبصورة خاصة عند المعاملة (L). أظهرت الدراسة إمكانية الانتخاب بصفة حجم الحبة ووزنها من أجل تحسين بعض الصفات الاقتصادية. The study targeted three durum wheat varieties Sham 1, Sham 3, Bohouth 5 and the variety Horani of the effects of three level (L, M. S) for the grain size and the thousand grain weight on the phonology periods and morphology characteristics. The study showed a positive relationship between the grain size and its weight ,on one side ,and between the percentage of in the laboratorian and field germination and the length of the coleoptile, the fast of the first growth (after a month of germination). The tillers beginning at the same time and the early ripening from the other side in the treatment of the only variety and among  the varieties, especially in the treatment (L). The three treatments were different within the same variety with significant difference in the tillers numbers characteristic in the one plant, and it was insignificant among the varieties inside the only treatment, and the Bohouth5 variety was superior in tillers numbers characteristic, and the early ripening especially in the treatment (L). This study showed  the selection ability in the size grain characteristic and its weight for the improvement of some  economical characteristics.